Information at equilibrium - Enrico Minelli; H. Polemarchakis (Brown University, Department of Economics, 2001)
In a game with rational expectations, individuals simultaneously refine their information with the information revealed by the strategies of other individuals. At a Nash equilibrium of a game with rational expectations, the information of individuals is essentially symmetric: the same profile of strategies is also an equilibrium of a game with symmetric information; and strategies are common knowledge. If each player has a veto act, which yields a minimum payoff that no other profile of strategies attains, then the veto profile is the only Nash equilibrium, and it is an equilibrium with rational expectations and essentially symmetric information; which accounts for the impossibility of speculation.
Keywords: D82; 330; Nash equilibrium; rational expectations; common knowledge; Nash-Gleichgewicht; Rationale Erwartung; Informationsökonomik; Theorie